Characterization and antibiogram profile of bacteria isolated from Buriganga river - Karim, Md Abdul; Happy, Rehena Nasrin (Bangladesh Journal of Botany, 2020)
Selected bacterial isolates from the surface water of Buriganga river were characterized by morphological, biochemical characteristics and sequence-based PCR-amplified fragments of 16S rRNA. All isolates were rod shaped and Gram-positive. The isolates were confirmed as Chryseobacterium arthrosphaerae strain FDAARGOS 519, Bacillus cabrialesii strain TE 3, Bacillus tequilensis KCTC strain 13622(T), Bacillus amyloliquefaciens DSM 7 strain ATCC 23350, Bacillus subtilis strain E20 and Bacillus subtilis subsp. subtilis strain 168 based on sequence analysis. A phylogenetic tree was constructed that showed only one major cluster comprising of two sub-clusters grouping Chryseobacterium arthrosphaerae in one and Bacillus tequilensis in another. Chryseobacterium arthrosphaerae strain FDAARGOS 519 was susceptible to all antibiotics at different ranges, while Bacillus tequilensis KCTC strain 13622(T) and Bacillus amyloliquefaciens DSM 7 strain ATCC 23350 were found to be resistant to polymyxin only but sensitive to other antibiotics. However, Bacillus cabrialesii strain TE 3 was resistant to polymyxin and neomycin, while Bacillus subtilis subsp. subtilis strain 168 was resistant to polymyxin, vancomycin and rifampicin.